The potency of clouthing on political expression and subjectivation of trans women (Novos Olhares, 2016)
The aim of this article is to show a fraction of a research intended to understand the connection between transgendered women's appearance and its potential politics. Observing concepts such as subjectivation, aesthetics and politics, used by Jacques Rancière, and the gender theory by Judith Butler, it pursuits, through semi-structured interviews, to find out how does those women use their visible resources to perform gender, and at the same time, show their systematic exclusion from the speech places existing on the social and civic sphere. We try to understand how women trans, particularly those interviewed in the research, can appropriate creatively of their bodies through the maquillage, the clothes, the care with the hair and other artifices that are part of the visible appearance, elaborating a singular and proper language and inventing a form of life whose power is exactly in the act to appear in public, in the construction of an argumentative and performative scene of enunciation livened up by the dissent.